PENGARUH TINGKAT KESEHATAN BANK TERHADAP KINERJA PERBANKAN SEKTOR FINANCIAL TECHNOLOGY BERBASIS DIGITAL BANKING YANG TERDAFTAR DI BURSA EFEK INDOENSIA TAHUN 2015-2020 - Agnes Santa; Tannia Tannia (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
The banking sector is one sector that has an important role for national economic development. Despite having an important role for a country's economy, banking in Indonesia is still quite vulnerable to several problems from various factors. Several issues in Indonesian Banking such as profitability, capital, non-performing loan and liquidity. A new problem that arises is the process of digitizing banking in Indonesia. With recent technological advancement, banks have to adapt with the innovation and implementation of digital banking. The purpose of this research is to measure and analyze the effect of several ratios that reflect the health of Indonesian banking on the financial performance of digital banking-based listed on the IDX. The data used in this study were taken from data on Indonesian banking financial ratios from 2015 to 2020. The number of samples used was 35 companies. The type of data used in this study is panel data, and the analysis technique used is panel data regression analysis. Simultaneous test results show that all independent variables (NPL, CAR, BOPO, NIM, and LDR) have a significant effect on ROA. The results showed that BOPO had a significant negative effect on ROA, while NPL, CAR, NIM, and LDR had no effect on ROA.